Analysis of Biomass Briquettes Made from Bagasse Using Tapioca Starch Adhesive with Drying Temperature Variations - Alfian, Devia Gahana Cindi; Saputra, Khamid Y. W.; Muhyi, Abdul; Silitonga, Dicky Januarizky (Jurnal Rekayasa Mesin, 2024)
Dependency on fossil fuels is making their availability increasingly scarce. Renewable energy is considered the best solution to replace fossil fuels, and at present, the primary focus should be on optimizing the utilization of renewable energy sources. As an example, biomass briquettes are being manufactured using bagasse and tapioca flour as adhesive in a 2:3 ratio. This study utilized a compression force of 50 kgf/cm2 and variations in drying temperatures (100 °C, 150 °C, and 200 °C) for 1 hour. The main objective of this research is to compare the quality of bagasse briquettes with the Indonesian National Standard (SNI) No. 01/6235/2000. The test results indicate that the best conditions were achieved at a drying temperature of 200 °C, with a moisture content of 4.47%, a calorific value of 5077.32 cal/g, a combustion rate of 0.1386 g/min, and carbon, volatile matter, and ash content percentages of 22.8333%, 26.845%, and 2.8323%, respectively.